PEDAGOGICAL DIRECTION IN THE POETICS OF VLADISLAV VLADIMIROV (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2026)
This article is devoted to the study of the pedagogical direction in the poetics of Vladislav Vladimirov, one of the significant representatives of modern Каzakh literature. In his work, pedagogical thought is revealed through poems, essays and publications, in which the author explores the role of the poet in society, upbringing and personal development, as well as the interaction of art and education. The main attention in the article is paid to the analysis of Vladimirov's poems, in which he touches upon issues related to education, morality and upbringing. The study compares the poet's pedagogical ideas with classical and modern theories of education, as well as with other Russian authors working in this direction. The article also examines the influence of pedagogical concepts on Vladimirov's work, revealing the features of their embodiment in the artistic form and structure of his works. In conclusion, the relevance of pedagogical themes in Vladimirov's poetry in the context of the modern literary process, as well as his contribution to the development of pedagogical thought through the prism of art, is examined.